Coiling of Very Large and Giant Basilar Tip Aneurysms: Midterm Clinical and Angiographic Results - van Rooij, W.J.; Sluzewski, M. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: The purpose of this study was to report the midterm clinical and angiographic results of coiling of very large (>15 mm) and giant basilar tip aneurysms.MATERIALS AND METHODS: Between January 1995 and October 2005, 44 very large and giant basilar tip aneurysms in 44 patients were coiled. There were 13 men (30%) and 31 women (70%) with a mean age of 51.4 years (median, 51 years; range, 34–72 years). Mean aneurysm size was 19.6 mm (range, 15–30 mm). Of 44 aneurysms, 33 (75%) had ruptured. Of 11 unruptured basilar tip aneurysms, 7 were incidentally discovered, 1 was additional to another ruptured aneurysm, and 3 were symptomatic by mass effect.RESULTS: Procedural mortality was 2/44 (4.6%, 95% confidence interval (CI), 0.4%–16%) and morbidity 1/44 (2.3%, 95% CI, 0.01%–13%). Of 33 patients with ruptured aneurysms, mean clinical follow-up was 5.2 years (range, 0.5–11.5 years). Two patients had a rebleeding from the coiled basilar tip aneurysm leading to death in 1 patient and to dependency in the other patient (annual rebleeding rate, 1.1%) One other patient died 2 years later of progressive brain stem compression. Mean angiographic follow-up in 41 of 42 surviving patients was 3.1 years. Nineteen aneurysms reopened and were coiled for a second time. Of these, 9 repeatedly reopened with time and were repeatedly coiled up to 6 times. Additional treatments were without complications.CONCLUSION: Coiling of very large and giant basilar tip aneurysms is associated with reasonably low morbidity. Although additional treatment during follow-up is frequently necessary, rebleeding is uncommon.